2015
DOI: 10.1523/jneurosci.1451-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Mediated Control of Spontaneous Bundle Oscillations in Saccular Hair Cells

Abstract: Hair cells of the vertebrate vestibular and auditory systems convert mechanical inputs into electrical signals that are relayed to the brain. This transduction involves mechanically gated ion channels that open following the deflection of mechanoreceptive hair bundles that reside on top of these cells. The mechano-electrical transduction includes one or more active feedback mechanisms to keep the mechanically gated ion channels in their most sensitive operating range. Coupling between the gating of the mechano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Bundles were found to oscillate at comparable amplitudes under coupled and uncoupled conditions. Since spontaneous oscillation was shown to correlate closely with opening and closing of the transduction channels [ 41 ], the presence of the microsphere did not significantly interfere with the transduction process.…”
Section: Methodsmentioning
confidence: 99%
“…Bundles were found to oscillate at comparable amplitudes under coupled and uncoupled conditions. Since spontaneous oscillation was shown to correlate closely with opening and closing of the transduction channels [ 41 ], the presence of the microsphere did not significantly interfere with the transduction process.…”
Section: Methodsmentioning
confidence: 99%
“…Transepithelial electrical stimulation was shown to trigger and entrain active bundle motility (Bozovic and Hudspeth, 2003). A combination of cell electrophysiology and mechanical bundle manipulation likewise demonstrated that membrane potential impacts active motility (Meenderink et al, 2015). Steady-state changes in the membrane potential were found to modulate the frequency, amplitude, and shape of spontaneous oscillations.…”
Section: Efferent Impact On Bundle Mechanics Is Consistent With Hypermentioning
confidence: 99%
“…Typical recordings are limited to observations of hair bundle mechanics, its oscillation and response to an imposed drive. Recently, recordings of bundle mechanics were combined with electrophysiological recordings of the cell soma, in spontaneously oscillating and driven bundles [40]. This technique allows the simultaneous probing of two variables, the hair bundle position X and the cell membrane potential V ss .…”
Section: B Lower Dimensional Projectionsmentioning
confidence: 99%
“…These recording conditions maintain the innate bundle oscillations, while providing access to the electrical state of the cell. These measurements were made in current-clamp mode, yielding data on the time-varying membrane potential [40]. The time delay in the voltage recording, due to the pipette resistance and the hair cell capacitance was on the order of ∼1 -2 ms. We neglect this in comparison to the bundle's time period ∼30 ms.…”
Section: B Comparison To the Three-dimensional Modelmentioning
confidence: 99%